2001
DOI: 10.1515/jpm.2001.036
|View full text |Cite
|
Sign up to set email alerts
|

Management trend and safety of vaginal delivery for term breech fetuses in a tertiary care hospital of Karachi, Pakistan

Abstract: Allowing trial of labor to carefully selected mothers can result in vaginal delivery in 77% of the cases. However, the risk of trauma and neonatal intensive-care unit admissions, among vaginal births may favor the decision of elective cesarean section, unless rigorous pre-delivery assessment and conduct of delivery by adequately trained obstetricians is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In another study conducted in Pakistan, from the study of 287 women where the causes of their previous caesarean section were breech birth, 77% of them had successful vaginal delivery. The results were fully compatible with our study (20).…”
Section: Discussionsupporting
confidence: 93%
“…In another study conducted in Pakistan, from the study of 287 women where the causes of their previous caesarean section were breech birth, 77% of them had successful vaginal delivery. The results were fully compatible with our study (20).…”
Section: Discussionsupporting
confidence: 93%
“…This was not the finding of others that found otherwise (8,13). However, it has been shown that in properly selected cases, slightly more than 70% of cases can be delivered vaginally with very little morbidity (21).…”
Section: Discussionmentioning
confidence: 99%